Acquisition of the Official Language for Children of Minorities at Latvian Preschool Educational Establishments: Evaluation of the Situation - Zariņa, Sandra; Mičule, Ilona; Silova, Larisa; Drelinga, Elga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the 21st century the issue about children of minorities, who in preschool beside their mother tongue also acquire the official language at a high level, is a pending matter. However, there are not any normative documents designed in Latvia, which would determine implementation of compulsory bilingual education programmes in preschool, therefore, the possibility for children of minorities to develop the skills of the official language at an early age is undertaken by teachers. The aim of the research is to evaluate the possibilities for children of minorities to acquire the official language at preschool educational establishments for minorities of Latvia and where the language of instruction is Latvian. During the research from October till December in 2014 (1) observations were made in 13 preschool groups with children of different age: in six groups where the language of instruction is Latvian and in seven groups of minorities, (2) three expert interviews with specialists of bilingual education were carried out. Opinions expressed by the experts correspond with the information obtained from the observations and confirm the idea, that a successful development of the Latvian language for children of minorities at an early age is promoted by (1) the official language skills and professional competence of the teachers, (2) the use of material resources and implementation of variedmethods during the game activities and after class activities, (3) cooperation between the teacher of Latvian, the group teacher and parents, (4) the teacher’s individual support and emotionally enabling environment.In the discussion the issue is being raised about the necessary support for preschool teachers’ work with children of minorities in preschool educational establishments for minorities and where the language of instruction is Latvian.